2009
DOI: 10.1143/jjap.48.04c172
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication and Photocurrent Generation Properties of Electrochemically Polymerized Fullerene–Poly(ethylene dioxythiophene) Composite Films

Abstract: Fullerene-poly(ethylene dioxythiophene) (polyEDOT) composite films consisting of 3,4-ethyeledioxythiophene (EDOT) and a thiophene derivative of C 60 fullerene (ThC 60 ) or C 60 fullerene were fabricated on a transparent indium-tin-oxide (ITO) electrode by electrochemical polymerization of the electrolyte solution of ThC 60 (or C 60 ) and EDOT. Incorporation of the C 60 fullerene moiety in the polythiophene film was strongly suggested from absorption spectra of the composite film. We have found a higher degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…[27][28][29][30][31] For instance, Benincori reported the first "charm bracelet"… [32] Akiyama et al have reported the electrochemical polymerization of thiophene-derivatized fullerene and EDOT to be used for higher incorporation of the fullerene moiety into the film. [33] Later on, Nasybulin et al developed an electrochemical approach to fabricate a solar cell based on a three-layer codeposition of PEDOT/poly(2,2´-bithiophene)/fullerene. [34] With all this in mind, in this work we prepared PEDOT-based thin films decorated with C60 fullerene.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31] For instance, Benincori reported the first "charm bracelet"… [32] Akiyama et al have reported the electrochemical polymerization of thiophene-derivatized fullerene and EDOT to be used for higher incorporation of the fullerene moiety into the film. [33] Later on, Nasybulin et al developed an electrochemical approach to fabricate a solar cell based on a three-layer codeposition of PEDOT/poly(2,2´-bithiophene)/fullerene. [34] With all this in mind, in this work we prepared PEDOT-based thin films decorated with C60 fullerene.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the immobilization of carbon nanomaterials within CPs solves this problem, improves the interconnections and homogeneously distributes the nanomaterial in the donor–acceptor junctions, providing a material with high efficiency. Multiple studies have been focused in obtaining a good distribution of the fullerene within the PEDOT matrix and avoid nanoparticle aggregation [ 35 , 36 , 37 , 38 , 39 , 40 ]. We have previously manufactured high quality PEDOT/C 60 films by co-electrodeposition with excellent C 60 homogeneity and high reproducibility with enhanced donor–acceptor interface, while retaining their bipolar conducting capabilities, i.e., both hole and electron transport [ 24 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, numerous experimental and theoretical results have revealed large enhancement in light absorption efficiency, fluorescence, surface-enhanced Raman scattering , (SERS), and photocurrents ,,, due to the proximal effects of NPs on conjugated polymers and dye systems. The observed enhancements are generally attributed to resonant coupling between radiation and particle plasmons in NPs and the possibility of tuning this resonance to coincide with the electronic transition levels of nearby molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently developed photoelectrodes using gold NPs with monolayers of organic dye molecules and demonstrated that photocurrents could be about 10–50 times enhanced as compared with the monolayer prepared on planar gold surfaces . We have also reported several different techniques to assemble plasmonic nanostructures on substrates, some of which include electrochemical deposition, electrostatic layer-by-layer adsorption of NPs, ,, vacuum deposition, and deposition of NP films formed on a liquid–liquid interface . More recently, we extended these studies to polythiophene, one of the most widely used conjugated polymer semiconductors in bulk heterojunction solar cells. ,, We observed appreciable enhancement of photocurrents in photoelectrodes consisting of gold NPs that were deposited on ITO substrates by electrostatic adsorption or electrodeposition and the polythiophene layer prepared by electropolymerization .…”
Section: Introductionmentioning
confidence: 99%